Rapid Monitoring of Vancomycin Concentration in Serum Using Europium (III) Chelate Nanoparticle-Based Lateral Flow Immunoassay - Bian, Lun; Liang, Junyu; Zhao, Hui; Ye, Ke; Li, Zhaoyue; Liu, Tiancai; Peng, Jie; Wu, Yingsong; Lin, Guanfeng (Frontiers in Chemistry, 2021)
Establishing personalized medication plan for patients to maximize therapeutic efficacy and minimize the toxicity of vancomycin (VAN) requires rapid, simple and accurate monitoring of VAN concentration in body fluid. In this study, we have developed a simple and rapid analytical method by integrate Eu (III) chelate nanoparticles (CN-EUs) and lateral flow immunoassay (LFIA) to fulfill real-time monitoring VAN concentration in serum within 15 min. This approach was performed on nitrocellulose (NC) membrane assembled LFIA strips via direct competitive immunoassay and exhibited a wide linear range of detection (0.1-80 μg*mL-1) with low limit of detection (69.2 ng*mL-1). The coefficient of variation (CV) of the intra- and inter-assay in detection of VAN were 7.12% to 8.53% and 8.46% to 11.82%, respectively. The dilution test and specificity indicated this method had stability that is not affected by serum matrix and some other antibiotics. Furthermore, the applicability of the proposed method was assessed by comparing the determined results with those measured by LC-MS/MS, performing a satisfactory correlation (R2=0.9713). The proposed CN-EUs-based LFIA manifested promising analytical performance, which showed potential value in real-time monitoring of vancomycin and could help optimize clinical use of more antibiotics.